1993
DOI: 10.1111/j.1432-1033.1993.tb18273.x
|View full text |Cite
|
Sign up to set email alerts
|

Limited proteolysis of yeast phosphofructokinase

Abstract: Purified phosphofructokinase 1 from baker's yeast (Saccharomyces cerevisiae) was subjected to proteol ysis by thermolysin, endoproteinase lys-C, trypsin and chymotrypsin under defined solvent conditions. In the absence of substrates and allosteric effectors, the catalytic activity of phosphofructokinase rapidly disappeared in the presence of each proteolytic enzyme. The presence of a saturating concentration of ATP protected phosphofructokinase activity from proteolytic inactivation while the collective presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 14 publications
2
29
0
Order By: Relevance
“…It has been observed that the presence of ATP protects Pfk in vitro from proteolytic inactivation (41). This has been proposed to be caused by conformational changes upon ATP binding.…”
Section: Fig 5 Heat Inactivation Of Pfk From Different Mutant Strainsmentioning
confidence: 99%
“…It has been observed that the presence of ATP protects Pfk in vitro from proteolytic inactivation (41). This has been proposed to be caused by conformational changes upon ATP binding.…”
Section: Fig 5 Heat Inactivation Of Pfk From Different Mutant Strainsmentioning
confidence: 99%
“…The mobility was related to the molecular masses of the premixed protein high-range molecular weight marker from Roche Molecular Biochemicals and purified native (21 S) as well as proteolytically degraded Pfk (12 S), for which molecular masses are well known (Kopperschläger et al, 1993). 1D-Gel analysis was done with the scanned SDS-PAGE images by using Labimage software version 2.6 (Kapelan GmbH, Halle, Germany).…”
Section: Sds-page and Western Blotmentioning
confidence: 99%
“…Denaturation of protein and SDS-PAGE were carried out according to Laemmli in 7.5% acrylamide running gels as described elsewhere (Kopperschläger et al, 1993) using the Mini-Protean II Dual Slab Cell system (Bio-Rad Laboratories). The mobility was related to the molecular masses of the premixed protein high-range molecular weight marker from Roche Molecular Biochemicals and purified native (21 S) as well as proteolytically degraded Pfk (12 S), for which molecular masses are well known (Kopperschläger et al, 1993).…”
Section: Sds-page and Western Blotmentioning
confidence: 99%
“…The stability of the oligomeric structure has been studied by means of different methods [9,11,12]. In dilution, the native enzyme was found to be a stable octamer down to nanomolar protein concentrations in the presence of ammonium sulphate.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the enzyme from most other organisms, which functions as homo-and heterotetramers, the yeast enzyme is a hetero-octamer composed of four α-and four β-subunits, which are arranged as a dimer of tetramers [6][7][8]. The subunits are each subject to limited proteolytic degradation in itro, involving primarily the N-terminal region of about 200 amino acids [9]. Careful preparation of phosphofructokinase in the presence of protease inhibitors, however, yields exclusively unprocessed subunits [10].…”
Section: Introductionmentioning
confidence: 99%